How do you solve sqrt(20-X) + 8= sqrt( 9-X) +11√20−X+8=√9−X+11?
2 Answers
Explanation:
Given,
sqrt(20-x)+8=sqrt(9-x)+11√20−x+8=√9−x+11
Subtract
sqrt(20-x)+8color(white)(i)color(red)(-8)=sqrt(9-x)+11color(white)(i)color(red)(-8)√20−x+8i−8=√9−x+11i−8
sqrt(20-x)=sqrt(9-x)+3√20−x=√9−x+3
Square both sides to get rid of the radical signs.
(sqrt(20-x))^2=(sqrt(9-x)+3)^2(√20−x)2=(√9−x+3)2
(sqrt(20-x))(sqrt(20-x))=(sqrt(9-x)+3)(sqrt(9-x)+3)(√20−x)(√20−x)=(√9−x+3)(√9−x+3)
Simplify.
20-x=(9-x)+6sqrt(9-x)+920−x=(9−x)+6√9−x+9
20-x=9-x+6sqrt(9-x)+920−x=9−x+6√9−x+9
2=6sqrt(9-x)2=6√9−x
Solve for
1/3=sqrt(9-x)13=√9−x
(1/3)^2=(sqrt(9-x))^2(13)2=(√9−x)2
1/9=9-x19=9−x
x=color(green)(|bar(ul(color(white)(a/a)color(black)(80/9)color(white)(a/a)|)))
Explanation:
Regrouping and powering
giving
Regrouping and powering
giving
Solving for